Collaborative Governance Untuk Pengembangan Sustainable Green Tourism Sebagai Upaya Pengentasan Kemiskinan (Discourse Network Analysis pada geopark.kebumenkab.go.id) - Salma Arum Hidayah; Rutiana Dwi Wahyunengseh (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2021)
This research is motivated by the problem of high poverty rates in Kebumen Regency. According to Badan Pusat Statistik (BPS) Jawa Tengah data, in 2019 Kebumen Regency has a poverty rate of 16,82%. This poverty rate is higher than the poverty rate in Central Java province and the national poverty rate. On the other hand, Kebumen Regency has great potential in the tourism sector with the existence of the Geopark KarangsambungKarangbolong (GKK). This Geopark is planned to reduce poverty rate in Kebumen Regency. The development is carried out in accordance with the concept of sustainable green tourism with collaborative governance principles. Various discourses on the development of this geopark are contained in online media in the form of a website, namely geopark.kebumenkab.go.id. This study uses the discourse network analysis (DNA) method to analyze news texts on the geopark.kebumenkab.go.id website starting from February 2019 to July 2020. The results of this study are a representation of collaborative governance for sustainable green tourism development as an effort to alleviate poverty, analysis of obstacles and opportunities for the development of the Karangsambung-Karangbolong Geopark (GKK), as well as mapping of actors involved in the discourse of developing the Karangsambung-Karangbolong Geopark.